ANALISIS IMPLEMENTASI PROFIL PELAJAR PANCASILA PADA SISWA SD NEGERI SEKARAN 01 KOTA SEMARANG - Afa Anisa Almas Soroya; Deni Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The independent curriculum is based on the development of the student's profile to have the soul and values contained in the pancasila's life. The purpose of this study is to analyze the implementation of student profile Pancasila in independent curriculum as student character reinforcement. The research was carried out at SD Negeri Sekaran 01 Kota Semarang which is one of the schools by applying an independent curriculum in its day-to-day. This research is a qualitative research with data capture techniques using source triangulation. The research subjects are students of the fourth grade of 28 students and the supporting sources are teachers of the Fourth grade and Head of State SD Sekaran 01 Kota Semarang. In its analysis, the study uses the Miles & Huberman model of: (1) data collection (2) data reduction (3) data presentation in the form of an outline or narrative text (4) conclusion drawings. The results were obtained, implementation of student profile Pancasila running in accordance with the guidelines of the student profile. The six aspects of the Pancasila student profile have been applied and have been embedded both in students both in intra-curricular, extracurricular activities as well as cochlear programs.